Genotoxic effects of profenophos on Pisum sativum - Anirup Sengupta; Rupak Kumar Sengupta (Journal of Agriculture and Applied Biology, 2021)
Profenophos is a commonly used organophosphate pesticide in pulse crops; however, it is difficult to say whether it is safe from cytogenotoxic effects. Test plant materials (field pea seeds) were soaked in 250 ml of 0.2%, 0.4% and 0.6% profenophos 50% EC separately for 6 hours. The mechanism behind various types of chromosomal anomalies observed due to treatment with profenophos has been discussed in detail. The effects of the pesticide that appeared in M1 generation diluted in M2. The appearance of C-metaphase with univalent and bivalents, multipolarities, chromatin bridges suggest that these organophosphate pesticides like profenophos affect genetic recombination which may lead to loss of important factors, gain of undesirable characters. This study aims at finding the cytological and genotoxic effect of pesticide profenophos on germ cells of Pisum sativum var. arvense and suggests judicious means of application of pesticides and agrochemicals in appropriate condition to elude further damages in the future.